Mobile Libraries and Digital Inclusion: A Study from Aotearoa New Zealand. Issue 1 (2nd January 2023) - Bell, Rachel; Goulding, Anne
ABSTRACT: Mobile libraries serve communities in a range of ways throughout Aotearoa New Zealand and internationally but their contribution to supporting digital inclusion in non-urban areas has not been explored in depth. T his paper presents data from an exploratory research project focused on how mobile libraries in Aotearoa New Zealand extend digital services to those who cannot access public library building s services conveniently. The findings show that the mobile librarians provide a range of digital inclusion services, predominantly access to technologies and skills development and, by so doing, contribute positively to digital inclusion in non-urban areas of Aotearoa New Zealand.